Dear bob and sue eaudiobook - Smith, Matt (Tantor Media, 2017)
Dear Bob and Sue is the story of our (Matt and Karen Smith's) journey to all 59 U.S. National Parks. We wrote the book as a series of emails to our friends, Bob and Sue, in which we share our humorous and quirky observations. It is at times irreverent, unpredictable and sarcastic, all in the spirit of humor. We describe a few of our experiences in each park but do not provide an exhaustive overview of each experience or park. We use these events as the vehicle to deliver insights about our relationship. We did not intend for this book to be a travel guide nor a recommendation for how to visit all 59 of the U.S. National Parks, although many readers have said they've found it to be a useful guide. Rather, it is our story about how we did it.